Personality and impulsivity as antecedents of occupational health in the construction industry. Issue 4 (2nd October 2022) - González-Recio, Sonia; Boada-Cuerva, Maria; Serrano-Fernández, María-José; Assens-Serra, Jordi; Araya-Castillo, Luis; Boada-Grau, Joan
Abstract: Objectives. In health and safety at work, two main groups of causes of occupational accidents have been identified: unsafe conditions or technical factors; and the causes related to safe behavior or the human factor. The objective of this study is to analyze the predictive variables (emotional intelligence, personality, impulsivity and safety of the work environment) for three factors of the CONS-32 scale (criterion variables: use of protections, personal risk behavior and personal physical workload) in the construction sector. Methods. Using a sample of 256 Spanish workers from this sector, we analyzed the significant correlations between the three criterion variables and a set of variables extracted from various instruments, as well as the regression models that explain most of the variance. Results. The results show that the main predictive variables that explain the three factors are those related to responsibility as a personality trait, impulsivity and safety of the work environment. Conclusions. Based on the empirical evidence found, the most explanatory factor in all cases is safety climate in the work environment.